PRAKTIK MANAJEMEN STRATEGIK DAN EFEKTIFITAS LAYANAN AKADEMIK PADA SEKOLAH MENENGAH PERTAMA BERBASIS PASENTREN: STUDI KASUS KUALITATIF - Nurbaiti Saliya; Ali Marzuki Zebua (Jurnal Manajemen Pendidikan, 2026)
This study aims to explore strategic management practices and analyze their contribution to the effectiveness of academic services in Islamic boarding schools (pesantren). The focus of the study includes the formulation, implementation, and evaluation of strategies and their relationship to the quality of academic services, such as consistency, assurance, responsiveness, empathy, and tangibles. The study used a case study design with a qualitative descriptive approach. Data were collected through structured interviews with the principal, vice principal, teachers, religious teachers (ustadz/ustadzah), and academic staff, as well as observations of learning and dormitory activities. Data analysis was carried out through reduction, presentation, and drawing conclusions with source triangulation to ensure data validity. The results of the study indicate that strategic management implemented collaboratively can improve the effectiveness of academic services. The strategy formulation involving stakeholders resulted in an integrated vision and mission between the Merdeka Curriculum and the Islamic boarding school curriculum. The strategy implementation supports holistic learning, while periodic evaluation encourages continuous improvement despite limitations in technology and measurable performance indicators.